Desarrollo de un plan de mantenimiento preventivo para los equipos de los talleres de Soldadura, Automatismos Mecatrónicos, Hidraulica y Refrigeración del Centro CIES del SENA de Cúcuta, Norte de Santander - Acosta Rozo, Rafael Andres
This project describes the design of a preventive maintenance plan for the equipment of the welding, mechatronics, hydraulics and refrigeration workshops of the CIES center of SENA Cucuta, whose main objective was to determine the maintenance management activities to be carried out in each of the teams of greater criticality and need of each formation. To achieve this, a series of consecutive stages was followed, starting with the inventory and diagnosis of the equipment belonging to the aforementioned workshops. Their current conditions were analyzed with the help of the instructors in charge, who with their experience allowed to develop this first stage. The heuristics of the instructors, the standard technical manuals and manufacturer's manuals for formulating the technical data sheets were taken into account as sources of information. Maintainability and criticality analyzes were performed on the inventoried teams, in order to rank them according to their level of importance for the training provided in each of the CIES center workshops. Subsequently, the analysis of modes and effects of AMEF failures were developed, which allowed to determine the failure modes that a team may have and their respective risk analysis. Throughout this process, a great deal of attention was paid to the proper development of the AMEF, and the other stages greatly influenced it. Finally, it was possible to establish the maintenance protocols to be performed, thanks to the use of decision sheets used in reliability-centered maintenance mythology (RCM). They determined the type and quantity of maintenance tasks to be performed according to the failure modes analyzed in the AMEF.